Underwater adhesive gel as well as preparation method and application thereof

A fluorinated ionic gel with enhanced mechanical and electrochemical properties addresses the challenges of underwater adhesion and self-healing in traditional hydrogels and ionogels, enabling effective underwater sensing and communication.

CN119119353AActive Publication Date: 2024-12-13SHANDONG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411210508.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-13
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

Traditional hydrogels and ionogels face challenges in achieving stable underwater adhesion due to hydration layer formation, swelling, and poor self-healing properties, limiting their application in humid and aquatic environments, especially for wearable sensors and communication devices.

Method used

A fluorinated ionic gel is prepared by copolymerizing 2,2,3,4,4-hexafluorobutyl acrylate and N-isopropylacrylamide in an ionic liquid, leveraging ionic dipole interactions and hydrophobicity to disrupt hydration layers and enhance mechanical and electrochemical properties, enabling strong underwater adhesion and self-healing.

Benefits of technology

The fluorinated ionogel exhibits excellent underwater adhesion, self-healing, and stability, facilitating applications such as underwater sensing, communication, and bioelectrode monitoring, with high conductivity and sensitivity across a wide strain range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119353A_ABST
    Figure CN119119353A_ABST
Patent Text Reader

Abstract

The invention discloses an underwater adhesive gel and a preparation method and application thereof.The preparation method of the underwater adhesive gel comprises the following steps that free radical copolymerization is conducted on 2, 2, 3, 4, 4, 4-hexafluorobutyl acrylate and N-isopropyl acrylamide in ionic liquid, and fluorine-containing ionic gel is prepared. And the copolymerized tough fluorine-containing gel material of the HFBA and the NIPAM is prepared. Due to the hydrophobicity of the fluorine-containing polymer and the ionic liquid, the interaction of ions and dipoles and the synergistic effect of molecular entanglement, the FIG has excellent water resistance, strong underwater binding power, excellent self-healing capability, excellent underwater stability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of gel technology, specifically relating to an underwater adhesive gel, its preparation method, and its application. Background Technology

[0002] The statements herein provide only background information in relation to this invention and do not necessarily constitute prior art.

[0003] Traditional hydrogels, when used as sensors, can adhere stably to human skin or other object surfaces. However, when applied in humid or underwater environments, moisture forms a hydration layer on both the substrate and the hydrogel surface, preventing contact between the gel and the substrate, resulting in reduced surface energy and decreased adhesion strength. Therefore, achieving strong and stable underwater adhesion is a significant challenge.

[0004] The development of ionogels with underwater adhesion, rapid self-healing properties, high transparency, stretchability, and multifunctionality is crucial for the development of underwater wearable sensors and communication devices. However, when traditional ionogels are applied underwater, they are prone to swelling, have poor adhesion, and are difficult to self-heal, making them unsuitable for high-intensity tasks and limiting their application range.

[0005] Furthermore, when using wearable sensors in humid, sweaty, or aquatic environments, some wearable sensors are attached by adhesive means. When these sensors come into contact with water, water molecules penetrate the skin-sensor surface and form a hydration film, reducing the interfacial adhesion between the sensor and the skin. This can lead to unstable monitoring results or cause the sensor to completely lose its adhesion to the skin and detach from the skin surface. Summary of the Invention

[0006] In view of the shortcomings of the existing technology, the purpose of this invention is to provide an underwater adhesive gel, its preparation method and application.

[0007] To achieve the above objectives, the present invention is implemented through the following technical solution:

[0008] In a first aspect, the present invention provides a method for preparing an underwater adhesive gel, comprising the following steps:

[0009] Fluorinated ionic gels were prepared by free radical copolymerization of 2,2,3,4,4,4-hexafluorobutyl acrylate and N-isopropylacrylamide in an ionic liquid.

[0010] HFBA is used to construct gel frameworks and exhibits excellent extensibility. However, gel materials obtained solely from the interaction of HFBA with ionic liquids lack sufficient mechanical strength. Introducing NIPAM enhances the properties of HFBA elastomers. On one hand, NIPAM, as a comonomer, can introduce hydrogen bonds, improving the mechanical strength of the gel. On the other hand, NIPAM is directly dissolved in [N8111]. + [TFSI] - In this process, no additional organic solvents are required, thus avoiding defects in gel performance.

[0011] This invention selects the flexible, hydrophobic polymer monomer 2,2,3,4,4,4-hexafluorobutyl acrylate (HFBA) and the hydrogen-bonded monomer N-isopropylacrylamide (NIPAM) for copolymerization in an ionic liquid. NIPAM, as a comonomer, can introduce dynamic bonds within the gel system, which is beneficial for improving the mechanical properties and interfacial adhesion properties of the ionic gel.

[0012] The quaternary ammonium cations in the ionic liquid and the -CF3 in the fluorinated polymer form an ionic dipole interaction, which increases the cohesive energy of the ionic gel and enhances its stability. Furthermore, the ionic liquid endows the gel with excellent electrochemical properties, exhibiting high conductivity and sensitivity over a wide strain range. Based on the hydrophobic properties of this fluorinated ionic liquid gel, it maintains good mechanical properties, electrochemical properties, self-healing properties, and anti-swelling properties in an aqueous environment, while effectively eliminating the interfacial hydration layer (in the fluorinated ionic gel prepared in this invention, due to the hydrophobic anion (TFSI)). - The presence of long hydrophobic carbon chains in ionic liquid cations and fluorinated side chains in polymers can disrupt the hydration layer barrier of the substrate and exclude interfacial water molecules, and achieve strong underwater adhesion to the substrate material through various interactions.

[0013] Based on the multifunctionality of this fluorinated ion gel, underwater sensing can be achieved, enabling rapid and sensitive underwater information exchange and communication, providing a new strategy for the application of next-generation flexible sensors in the ocean and other aquatic environments.

[0014] In some embodiments, the molar ratio of 2,2,3,4,4,4-hexafluorobutyl acrylate to N-isopropylacrylamide is 10:1-8.

[0015] Preferably, the molar ratio of 2,2,3,4,4,4-hexafluorobutyl acrylate to N-isopropylacrylamide is 2:1. The polymer exhibits optimal performance when the molar ratio of HFBA to NIPAM is 2:1. Further increases in the HFBA content decrease the gel's mechanical strength; conversely, increases in the NIPAM content cause the gel to harden and reduce its electrical conductivity.

[0016] Preferably, the temperature for free radical copolymerization in the ionic liquid is 20-60℃, and the copolymerization time is 4-10h.

[0017] Preferably, a photoinitiator is added during the copolymerization process, and ultraviolet light is applied.

[0018] In some embodiments, the ionic liquid is [N8111]. + [TFSI] - Ionic liquids.

[0019] Preferably, the ionic liquid is prepared by mixing lithium bis(trifluoromethanesulfonylimide) and octyltrimethylammonium chloride in water, stirring vigorously, and after phase separation, the lower oil phase is the ionic liquid.

[0020] A further preferred embodiment includes the step of repeatedly washing and drying the obtained ionic liquid.

[0021] In a further preferred embodiment, the obtained ionic liquid is repeatedly washed with deionized water 3-7 times.

[0022] More preferably, the drying is vacuum drying, the drying temperature is 60-80℃, and the drying time is 10-14h.

[0023] More preferably, the molar ratio of lithium bis(trifluoromethanesulfonylimide) and octyltrimethylammonium chloride is 1:0.8-1.2.

[0024] Further preferably, 0.5-1.5 mol of lithium bis(trifluoromethanesulfonyl)imide and 0.5-1.5 mol of octyltrimethylammonium chloride are added per liter of water.

[0025] Secondly, the present invention provides an underwater adhesive gel prepared by the aforementioned preparation method.

[0026] Thirdly, the present invention provides the application of the underwater adhesive gel in the preparation of underwater sensors, including but not limited to optical camouflage elements, motion detection elements, underwater communication elements, water temperature detection elements, water pressure detection elements, or electrocardiogram detection elements.

[0027] The beneficial effects achieved by one or more embodiments of the present invention described above are as follows:

[0028] Due to fluorine's high electronegativity and the highly polarized CF bond, its large dipole moment and the well-established dipole-dipole and ion-dipole interactions between the CF bond and its surrounding environment make fluorinated polymers ideal polymer matrices for preparing ionogels. These matrices exhibit low surface energy and excellent thermochemical stability. Ionic liquids interact with polymer chains through ion-dipole interactions, increasing the crosslinking density of the gel. The poor hydrogen donation and acceptance properties of the CF bond result in weak interactions between fluorinated polymers and fluorine-rich ionoliquids and water molecules, minimizing interference from the aqueous environment on ion-dipole interactions and exhibiting high humidity insensitivity. Furthermore, the steric hindrance provided by the fluoropropylene ester in HFBA offers more free volume for moving ions, which is beneficial for improving the ionic conductivity and underwater self-healing capabilities of fluorinated ionogels.

[0029] The fluorinated ionogel (FIG) of this invention is produced using a one-step method, eliminating the need for chemical cross-linking agents in [N8111]. + [TFSI] - A copolymer of HFBA and NIPAM was prepared. Due to the synergistic effect of the hydrophobicity of the fluoropolymer and ionic liquid, ion-dipole interactions, and molecular entanglement, FIG exhibits excellent water resistance, strong underwater adhesion, excellent self-healing ability, and outstanding underwater stability.

[0030] FIG-based gel sensors exhibit excellent sensing performance in underwater environments, enabling optical camouflage, motion detection, and unimpeded communication in seawater, which is of great significance for aquatic environment exploration. They can also fulfill specific functions, such as detecting changes in water temperature and pressure, recognizing underwater human movements, long-term monitoring of electrocardiogram signals in aquatic environments, and even promoting rapid adhesion and repair of biological tissues. These attractive properties indicate that the developed super-stretchable and rapidly self-healing fluorinated ionomer gel with unique underwater camouflage and self-adhesive properties is a promising candidate, especially for wearable strain sensing and communication applications in aquatic and complex environments.

[0031] Electrocardiograms (ECGs) record electrical signals, alerting people to take preventative measures before a heart attack and sending out distress alerts when one occurs. This is crucial for exercise management and healthcare. While real-time monitoring of human ECG signals has been achieved in air, implementing ECG monitoring in aquatic environments remains challenging. A major limitation is that interfacial electrodes may lose their function underwater. Gels with high intrinsic conductivity and adhesion show great promise in the field of bioelectrodes. As previously demonstrated, FIGs possess stretchability, conductivity, underwater self-healing ability, underwater adhesion, and underwater stability, making them suitable as bioelectrodes for underwater ECG monitoring. Attached Figure Description

[0032] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0033] Figure 1 a) Schematic diagram of the ionogel structure and interactions between components. b) Photograph of FIG-40 loaded with 1 kg without breakage. Sample dimensions: 1 mm thickness, 10 mm width. c) Transmittance of an ionized gel with a thickness of 1.5 mm in the visible light wavelength range; Inset: Photograph of the ionogel; d) Relationship between the ionic conductivity of the ionogel and the IL content;

[0034] Figure 2 These are characterization images of the self-healing properties of ionogels, including: a) a photograph of the underwater self-healing process of the ionogel; b) tensile stress-strain curves of the original and repaired samples in air and water after 12 hours; c) tensile stress-strain curves of the repaired samples at different times; d) the relationship between self-healing efficiency and healing time; e) tensile stress-strain curves of the original and repaired samples in different media; f) optical microscopic images of FIG-40 after cutting and self-healing in water for 12 hours; g) FIG-40 at 5 rad s. -1 Oscillation amplitude scan test at angular frequency; h) Cyclic strain scan rheological test of FIG-40 at shear strain of 1% and 200% for 25 seconds; i) Self-healing process of FIG-40's electrical properties; j) Images showing FIG-40's ability to recover electrical properties.

[0035] Figure 3 In the figures, a) Water contact angle (WCA) graphs of FIG with different [N8111][TFSI] contents; b) Peel shear curves and adhesion strength graphs of FIG with different [N8111][TFSI] contents in an aqueous environment; c) Adhesion strength graphs of FIG with different [N8111][TFSI] contents to glass in an aqueous environment; d) Adhesion strength graphs of FIG-40 at different water temperatures; e) Adhesion behavior of FIG to glass, polypropylene (PP), aluminum, and rubber underwater; f) Adhesion strength graphs of FIG-40 to different substrates in air and underwater; g) Adhesion mechanism between FIG and substrate; h) Adhesion strength graphs of FIG-40 to glass in different solutions; i) Graphs showing the application of FIG-40 in repairing leaked silicone tubing; j) Comparison of FIG-40 with previously reported underwater adhesive gels in terms of adhesion strength and other physical properties.

[0036] Figure 4In the diagram, a) a FIG-40-based sensor can monitor finger bending at different angles in the aquatic environment in real time by changing relative resistance; b) Morse code diagram. The ionogel sensor communicates underwater via Morse code; attempts to express c) "SOS", d) "HELP" and e) "dangerous"; f) sensor detects hand gesture changes; g) relative resistance change of FIG-40-based sensor in salt solutions with different NaCl contents; h) conductivity change of FIG-40 at different salt concentrations; real-time sensing signals of different swimming states of a shark model, including i) slow and j) fast; k) conductivity change of ionogel with temperature; l) relative resistance change of ionogel sensor during cyclic temperature changes (from 35°C to 40°C).

[0037] Figure 5 In the diagram, (a) is a schematic diagram of an ion gel electrode used for electrocardiogram (ECG) monitoring, (b) ECG waveforms measured by the ion gel electrode: at rest and during movement, (c) is an enlarged view of the ECG waveform, (d) is an ECG waveform measured by a commercial electrode: at rest and during movement, (e) is a schematic diagram of an ion gel electrode used for underwater physiological signal monitoring, and (f) is an ion gel electrode and a commercial electrode used for underwater physiological signal monitoring. Detailed Implementation

[0038] It should be noted that the following detailed description is illustrative and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0039] The present invention will be further described below with reference to the embodiments.

[0040] Example 1

[0041] Material

[0042] Lithium bis(trifluoromethanesulfonylimide) (LiTFSI), octyltrimethylammonium chloride ([N 8111 2,2,3,4,4,4-Hexafluorobutyl acrylate (HFBA) and N-isopropylacrylamide (NIPAM) were purchased from Shanghai Maclean Biotechnology Co., Ltd. 2,2-Diethoxyacetophenone was purchased from TCI. All water used in the experiments was deionized water; no further purification was required for any reagents.

[0043] The preparation method of underwater adhesive gel includes the following steps:

[0044] 1) Synthesis of ionic liquids

[0045] First, 0.01 mol of [N8111]Cl and 10 mL of LiTFSI solution (1 mol / L) were vigorously stirred at room temperature. After phase separation, the lower oil phase was collected and washed five times with deionized water. Then, it was dried under vacuum at 70 °C for 12 hours to obtain a colorless and transparent ionic liquid, [N8111]. + [TFSI] - The yield was 85.7%.

[0046] 2) Preparation of Fluorine Ion Gel (FIG)

[0047] 0.027g DEAP (photoinitiator 2,2-diethoxyacetophenone), 2.0167g HFBA, 0.4833g NIPAM and 1g [N8111] were added. + [TFSI] - Mix thoroughly to obtain a mixed solution.

[0048] The mixed solution was then poured into a polytetrafluoroethylene mold and reacted under ultraviolet light (365nm, 32W) for 4 hours to finally obtain a fluorinated ion gel.

[0049] Performance testing:

[0050] Using a Bruker's Avance III 400MHz nuclear magnetic resonance spectrometer, with deuterated chloroform as solvent and tetramethylsilane as internal standard, the following analysis was performed. 1 H-NMR spectral analysis.

[0051] Fourier transform attenuated total internal reflection (ATR) method was used to record FTIR spectra on a Nicolet iS10 Fourier transform infrared spectrometer. The infrared light was scanned 64 times, with a frequency range of 4000-400 cm⁻¹. -1 .

[0052] The transparency of a 1.5 mm thick ionogel was tested using an Agilent Cary 5000 UV-vis-NIR spectrophotometer in the wavelength range of 400-800 nm.

[0053] Differential scanning calorimetry (DSC) measurements were performed on a DSC25 thermal analyzer under N2 protection at a heating rate of 10 °C / min, with a temperature range of -60 °C to 40 °C.

[0054] First, the molar ratio of HFBA and NIPAM was optimized:

[0055] DEAP's mass percentage is 1%, [N8111] + [TFSI] -The mass percentage is 20%, and the molar ratios of HFBA and NIPAM are 10:3, 10:4, 10:5, 10:6, and 10:7, respectively.

[0056] Figure 1 The preparation process of fluorinated iontophoresis gel is demonstrated, which involves using HFBA, NIPAm, and [N8111]. + [TFSI] - The uniform and transparent precursor solution of DEAP was transferred into a polytetrafluoroethylene mold with a silicone pad fixed, and then subjected to ultraviolet light polymerization to form a uniform gel.

[0057] The tensile testing method was as follows: the mechanical properties of the ionogel were tested using a Spirax universal tensile testing machine equipped with a 50N sensor. The ionogel was cut into rectangular specimens (30 mm long and 5 mm wide). The tensile rate for all tests was fixed at 50 mm / min. The stress (σ) was calculated by dividing the test force by the original average cross-sectional area, and the strain (ε) was calculated by dividing the tensile length by the initial length of the specimen. All mechanical tests were repeated at least five times, and the results were averaged to ensure the accuracy of the experimental results.

[0058] HFBA is used to construct gel frameworks and exhibits excellent extensibility. However, gel materials obtained solely from the interaction of HFBA with ionic liquids lack sufficient mechanical strength, with a tensile strength of only 38 kPa. Therefore, NIPAM is introduced to enhance the properties of HFBA elastomers. On one hand, NIPAM, as a comonomer, can introduce hydrogen bonds, improving the mechanical strength of the gel; on the other hand, NIPAM is directly dissolved in [N8111]. + [TFSI] - No additional organic solvents are required, thus avoiding defects in gel performance. It has been confirmed that the optimal performance is achieved when the molar ratio of HFBA to NIPAM in the polymer is 2:1. If the HFBA content is further increased, the mechanical strength of the gel will decrease; on the other hand, increasing the NIPAM content will harden the gel and reduce its conductivity. Therefore, by maintaining a fixed molar ratio of HFBA to NIPAM of 2:1, the resulting fluorinated ionogel can withstand a weight of 1 kg without breaking (the gel is adhered to a 1 kg object with a contact area of ​​2.5 × 2.5 cm). 2 Then, the lifting gel can lift the adhered object. Figure 1 b).

[0059] For wearable sensor devices, transparency is a key parameter, enabling not only real-time observation and monitoring of interfaces such as skin, but also optical camouflage when necessary. The P(HFBA-co-NIPAM) copolymer matrix is ​​colorless, transparent, and highly tough.

[0060] like Figure 1As shown in Figure c, the prepared ionic gel, with a thickness of 1.5 mm, achieved a transparency of 90%, demonstrating strong potential as a skin sensor. The introduced NIPAM fragment improved the gel's mechanical properties, while the hydrophobic HFBA fragment facilitated compatibility between the polymer matrix and the ionic liquid (IL) and its stability in water. Due to the high electronegativity of fluorine atoms and the low surface energy of CF bonds, the HFBA fragment, rich in CF bonds, served as a functional component, enhancing the polarity and hydrophobicity of the polymer matrix. Similarly, the ionic liquid [N8111] also contains CF bonds. + [TFSI] - It also contributes to hydrophobicity. Furthermore, due to the fluoride ion-cation interaction between them, [N8111] + Cations tend to be attracted to HFBA fragments in the P(HFBA-co-NIPAM) copolymer matrix. The ionic conductivity also exhibits highly tunable characteristics by changing the IL content in the ionogel.

[0061] like Figure 1 As shown in d, with a fixed molar ratio of HFBA to NIPAM of 2:1 and a DEAP mass percentage of 1%, when [N8111] + [TFSI] - When the content increased from 20 wt% to 60 wt% (specifically 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, and 70 wt%), the ionic conductivity showed a linear increasing trend on a logarithmic scale, from 4.4 × 10⁻⁶. -4 S·cm -1 Increase to 2×10 -3 S·cm -1 This represents an increase of approximately one order of magnitude. The high ionic conductivity can be attributed to the enhanced interaction between fluoride ions and cations.

[0062] In the fluorinated ion gel prepared in this invention, due to the hydrophobic anion (TFSI) - The presence of long hydrophobic carbon chains in ionic liquid cations and fluorinated side chains in polymers can disrupt the hydration layer barrier of the substrate, excluding interfacial water molecules. This is evidenced by water contact angle measurements of FIGs with different IL contents. Figure 3 As can be seen, when the IL content increases from 20wt% to 60wt%, the water contact angle increases from 92.6° to 115.6°, and the fluorinated ion gel FIG exhibits obvious hydrophobicity.

[0063] The shear test procedure is as follows: The ionogel is attached to the surface of one substrate, and then overlapped with another substrate, with a contact area of ​​2.5 × 2.5 cm. 2The samples were pre-compressed in an aqueous environment for 12 hours to obtain adhesion test samples. The test samples were then removed from the aqueous environment and immediately pulled at a fixed speed of 50 mm / min on a Spirax universal tensile testing machine until separation occurred under ambient conditions. The adhesion strength was calculated by dividing the maximum load by the initial adhesion area.

[0064] The adhesion properties of FIG to the substrate material (glass) were quantitatively tested using an overlap shear test. Generally, adhesion failure occurs in two forms: deadhesion occurs within the ionogel adhesive (cohesive fracture) or at the bonding interface (interfacial fracture), depending on the location of the weakest point. Therefore, the apparent adhesion strength of fluorinated ionogels is limited by cohesive force and the minimum interfacial adhesion strength.

[0065] from Figure 3 As can be seen from Figures b and c, as the IL content decreases from 70 wt% to 40 wt%, the adhesion strength of FIG increases from 176 ± 8 kPa to 318 ± 39 kPa due to the denser cross-linked network of FIG, reduced plasticizing effect of ionic liquid, increased mechanical strength, and increased cohesion.

[0066] When the IL content is further reduced from 40wt% to 20wt%, although the mechanical strength of the ionogel is further improved, its adhesive strength decreases to 185±9kPa. This is because the high modulus prevents the ionogel from forming a full contact interface with the glass surface, resulting in low adhesive strength. Considering cohesion, interfacial adhesion, and interfacial compatibility, FIG-40 (IL content of 40wt%) exhibits the highest adhesive strength to glass.

[0067] The ionogel prepared by this invention maintains stable adhesion properties over a wide temperature range. Whether in low-temperature or high-temperature environments, the gel retains its structural integrity and adhesive ability. This temperature stability allows the ionogel to reliably adhere to the substrate surface over a wide temperature range without losing adhesion due to temperature changes. Figure 3 Figure d shows the underwater adhesion strength of FIG-40 at different temperatures. The ionogel was attached to the surface of one substrate and then cross-overlaid with another substrate, with a contact area of ​​2.5 × 2.5 cm. 2 The samples were pre-compressed in an aqueous environment for 12 hours to obtain adhesion test samples. The test samples were then removed from the aqueous environment and immediately pulled at a fixed speed of 50 mm / min on a Spirax universal tensile testing machine until separation occurred under ambient conditions. The adhesion strength was calculated by dividing the maximum load by the initial adhesion area.

[0068] Typically, the adhesive strength of iontophoretic adhesives decreases significantly at low temperatures. This is mainly because as temperature decreases, the molecular motion of polymer chains slows down, making it difficult for the gel interface to form various interactions with the substrate material. However, compared to most other gel materials, FIG-40 maintains a high level of adhesive strength even at low temperatures (4°C), and its adhesive strength can even reach 175 kPa in a relatively low-temperature aqueous environment. This can be explained by P(NIPAM-co-HFBA) and [N8111]. + [TFSI] - There exists a UCST, or high critical solution temperature. When the temperature is below the UCST, the hydrogen bonding interactions between P(NIPAM-co-HFBA) copolymers increase, and the intermolecular forces are strengthened, which improves the cohesiveness of the ionogel. Therefore, the thermal responsiveness of the NIPAM polymer can minimize the adhesion degradation caused by this low temperature, thus broadening the application temperature range of the ionogel.

[0069] To further evaluate the adhesion properties of FIG to different substrate materials. Figure 3 The data shows that FIG can tightly adhere to and rapidly lift various substrate materials in an aqueous environment, such as glass, PP (plastic), aluminum (metal), and rubber. In an aqueous environment, the adhesion strengths of this fluorinated ionogel to glass, copper, steel, aluminum, PMMA, titanium, rubber, PET, and pigskin are 318 kPa, 404 kPa, 305 kPa, 243 kPa, 258 kPa, 382 kPa, 186 kPa, 232 kPa, and 34 kPa, respectively. Compared to adhesion in air, the adhesion strength did not change significantly (e.g., ...). Figure 3 (as shown in f) is superior to most reported underwater adhesive gels.

[0070] This demonstrates that FIG can achieve rapid and strong underwater adhesion to various substrate materials. The strong adhesion is likely due to the synergistic effect of chemical bonds and energy dissipation during the peeling process. Fluoride ionogels contain numerous cations and anions, as well as polar groups such as amides, carbonyl groups, trifluoromethyl groups, and sulfonyl groups. These groups can provide strong adhesion to different substrates through various interactions, including electrostatic interactions, hydrogen bonds, ionic dipole interactions, cation-π interactions, van der Waals forces, and hydrophobic interactions, thereby achieving underwater adhesion. Figure 3 g).

[0071] Furthermore, the cationic groups can expel surface salt ions from the matrix, thus providing the possibility of adhesion in seawater and other salt solutions. Experiments have confirmed that the ionogel maintains excellent adhesion strength in various water bodies, including seawater, saline, acidic solutions, and alkaline solutions. Figure 3h). In acidic and alkaline solutions, the adhesion strength of the ionogel hardly decreased, indicating that the ionogel has strong pH adaptability. However, the adhesion strength decreased slightly in physiological saline and seawater, which may be because the salt ions in the solution disrupted some of the ion dipole interactions in the FIG. Strong underwater adhesion is beneficial for the practical application of ionogel sensors and the accurate acquisition and output of sensing signals.

[0072] As a demonstration, this iontophoresis adhesive was used to quickly repair leaks in silicone pipes, immediately stopping the leakage. Figure 3 i).

[0073] To demonstrate the advantages of FIG-40 among reported underwater adhesive gels, a detailed comparison was made of FIG-40's underwater adhesion strength, stretchability, tensile strength, transparency, and anti-swelling properties, such as... Figure 3 As shown in Figure j, the ionogel based on fluorinated copolymers and IL exhibits broad environmental adaptability, strong adhesion, and does not require specific functional groups during adhesion. The excellent underwater adhesion properties of this fluorinated ionogel are of great significance for the application of gel-based sensors in underwater monitoring.

[0074] FIG-40 exhibits excellent underwater adhesion strength to various substrates and demonstrates electrical stability under mechanical deformation, making it possible to detect human movement in aquatic environments. For example... Figure 4 As shown in Figure a, a FIG-40 base sensor (size: 1cm × 2cm, directly adhered to the finger by iontophoresis) is fixed to the finger to monitor its bending motion underwater. When the extended finger gradually bends from 0° to 90°, the relative resistance increases synchronously with the increase in the degree of bending due to stretching. Conversely, when the finger returns to its extended state, the output signal strength gradually decreases, returning to its original value, and this signal can be repeated. Furthermore, the trend of relative resistance change can also indicate changes in finger behavior. For example, an increase in relative resistance indicates that the finger is bending, while a decrease in signal strength indicates that the bent finger is straightening.

[0075] Morse code is composed of dots and lines; these dots are arranged in different ways to represent different letters, making it an effective method of information communication. Figure 4(b) Ionogels possess good durability and stability, maintaining their shape and performance over extended periods. This means that the resulting ionogel Morse code can remain readable and functional for a considerable time, unaffected by environmental factors. Since the relative resistance change of the FIG-40-based sensor is stable while maintaining the same operational state, Morse code can be generated based on the duration of finger bending. Rapid bending produces a spike-like electrical signal, representing a "point," while prolonged bending produces a straight line, representing a "line." Therefore, information can be conveyed in this way. The sensor is attached to the finger joint, and the finger is rhythmically bent in an aqueous environment. Figure 4 Test results c, d, and e show that, just like in air, the sensor's resistance changes rapidly as the finger bends, and FIG-40 can easily generate "SOS," "HEIP," and "dangerous" signals in water. This indicates that FIG-40 has underwater motion monitoring capabilities and can achieve underwater communication.

[0076] By deforming or compressing the gel material, minute changes in water pressure can be detected in real time, making it highly effective in water pressure monitoring and control applications. When water pressure changes, the gel sensor can quickly sense it and output a corresponding signal. This fast response time makes gel sensors ideal for applications requiring real-time monitoring and control of water pressure. Figure 4 As shown in f, the resistance changes in real time as the hand enters the water. The change in relative resistance reaches its maximum after the entire hand is submerged, indicating that the sensor can accurately distinguish the hand gestures entering the water. More importantly, this fluorinated ionogel sensor can also sense different depths in water and stably detect signal changes.

[0077] Meanwhile, the ionogel prepared by this invention can resist the erosion of chemicals, salts, and other corrosive substances in water, thereby extending the sensor's service life and improving its stability. Some natural water bodies, such as seawater or salt lakes, contain a certain concentration of salt. Therefore, the ionogel was immersed in NaCl aqueous solutions of different concentrations to study its practicality in real water environments.

[0078] like Figure 4 As shown in g,h, although the relative resistance decreases rapidly as the NaCl content increases from 0 wt% to 4 wt%, this decrease in sensing intensity is attributed to the increase in the ionic conductivity of the solution. However, even at the high NaCl content of 4 wt%, the detection signal remains accurately discernible, demonstrating the sensing feasibility of the ion gel sensor in high-ionic solutions (0.325 S / cm, 4 wt% NaCl solution) and its applicability to most natural water bodies.

[0079] FIG-40-based sensors were attached to an underwater animal model (shark model) to detect its movement in simulated seawater. The sensor was attached to one side of the shark model's tail to continuously capture electrical signals from the tail's wagging motion during swimming. Various swimming patterns of the shark (including resting, slow swimming, fast swimming, leaping out of the water, turning right, and turning left) manifested as multiple electrical signal patterns. For example, swimming speed could be assessed by signal frequency, as speed is determined by the frequency of tail wagging. When the shark turns right or left, its tail bends to the left or right for a longer period, and the ionogel sensor is correspondingly under tension or compression. Figure 4 Therefore, the direction of the turn can be determined by the signal strength and duration. Simultaneously, the significant difference in conductivity between simulated seawater and air causes drastic changes in signal strength, which can be used to determine whether the shark has leaped out of the water.

[0080] Water temperature is a crucial parameter for aquatic environment monitoring. Gel sensors can monitor water temperature changes in real time, helping to understand the thermal characteristics, seasonal variations, and biological activity of water bodies. Abnormal water temperature changes may be related to natural disasters (such as floods and droughts) or human factors (such as industrial wastewater discharge). Timely monitoring of water temperature through gel sensors can provide early warning information, helping to predict and respond to potential aquatic environmental problems, and taking necessary measures early to reduce losses and protect public safety. This is of great significance for environmental science, water resource management, and ecological protection. The conductivity of ionomers shows a linear increasing trend with increasing temperature. Figure 4 This is mainly because as the temperature increases, ions in the ionogel gain more thermal energy, increasing their velocity and thus the diffusion coefficient of ions within the ionogel. The high-speed movement of ions and the increased diffusion coefficient promote charge transport, thereby improving conductivity.

[0081] Furthermore, the conductivity of this fluorinated ion gel exhibits periodic changes with increasing and decreasing temperature. Figure 4 The primary reason for this is that ionogels contain temperature-sensitive polymer components that undergo phase transitions within a specific temperature range. Above or below the phase transition point, the polymer structure changes significantly, thus affecting conductivity. For example, at relatively low temperatures, the polymer is in a highly cross-linked state with low ionization and low conductivity; while as the temperature rises, the polymer chain conformation may become looser, facilitating ion transport and leading to an increase in conductivity. Therefore, this phase transition process results in periodic variations in conductivity, making this fluorinated ionogel a potential application in temperature-sensitive sensors, smart materials, and other fields.

[0082] FIG ion gel electrodes were attached to the human body, and their electrocardiogram monitoring performance in air was characterized. Figure 5a). When volunteers are resting, the iontophoresis electrodes can accurately record their voltage signals, and due to the good adhesion of the iontophoresis gel to the skin, it can still stably transmit electrocardiogram signals when volunteers start exercising, allowing for real-time monitoring of their health status. Figure 5 b). From Figure 5 As can be seen, FIG iontophoresis gel electrodes can accurately record ECG signals and clearly distinguish P, Q, R, S, and T waves. It can also be seen that there is no difference in ECG monitoring compared to commercial gel electrodes (CGE). Figure 5 d) indicates that the ion gel electrode has the same ECG detection capability as commercial electrodes in air.

[0083] Compared to commercially available gel electrodes, FIG ionogel electrodes exhibit superior underwater electrocardiogram (ECG) monitoring capabilities. Traditional bioelectrodes often fail to adhere well to the skin in aquatic environments, resulting in inaccurate ECG signal detection. For example... Figure 5 As shown in Figure e, when the electrode is attached to the human body surface and moved underwater, the CGE quickly (within 10 minutes) detaches from the skin and loses its ECG monitoring capability. In contrast, the iontophoresis electrode exhibits strong adhesion, enabling continuous and stable recording of ECG signals underwater. Figure 5 f) demonstrates the ability of ionogel electrodes to detect electrocardiogram signals over long periods in an aqueous environment. Importantly, the ionogel electrode combines self-adhesion and intrinsic conductivity. Compared to existing commercial electrodes, the FIG-40 ionogel electrode does not require additional adhesion and conductive layers. Furthermore, FIG-40 can be prepared via simple one-step free radical polymerization, significantly simplifying the fabrication process of bioelectrodes and demonstrating broad promise in the field of health monitoring.

[0084] Comparative Example

[0085] Without NIPAM, consisting only of the monomers HFBA and [N8111] + [TFSI] - The prepared ionogel was tested for its adhesion properties. The preparation method was the same as in Example 1.

[0086] The results showed that the adhesion strength of the ionogel without NIPAM decreased significantly, as did [N8111]. + [TFSI] - When the content accounts for 40 wt% of the total monomer mass, its adhesion strength (glass) is only 43.4 kPa, which is far lower than that of FIG-40. This is attributed to the fact that the ionogel without NIPAM has weak internal interaction forces and an insufficiently dense cross-linked network, resulting in too low cohesion and insufficient adhesion strength.

[0087] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing an underwater adhesive gel, Features: The steps include: Fluorine-containing ion gel was prepared by free radical copolymerization of 2,2,3,4,4,4-hexafluorobutyl acrylate and N-isopropylacrylamide in ionic liquid.

2. The method for preparing the underwater adhesive gel according to claim 1, Features: The molar ratio of 2,2,3,4,4,4-hexafluorobutyl acrylate to N-isopropylacrylamide is 10:1-8.

3. The method for preparing the underwater adhesive gel according to claim 1, Features: The temperature of free radical copolymerization in ionic liquid is 20-60°C, and the copolymerization time is 4-10h.

4. The method for preparing the underwater adhesive gel according to claim 3, Features: During the copolymerization, a photoinitiator is added and ultraviolet light is applied.

5. The method for preparing the underwater adhesive gel according to claim 1, Features: The ionic liquid is [N8111] + [TFSI] - Ionic liquids.

6. The method for preparing the underwater adhesive gel according to claim 5, Features: The preparation method of the ionic liquid is as follows: lithium bis(trifluoromethanesulfonyl)imide and octyltrimethylammonium chloride are mixed in water, and stirred vigorously, and after phase separation occurs, the oil phase at the bottom is the ionic liquid.

7. The method for preparing the underwater adhesive gel according to claim 6, Features: The step of repeatedly washing and drying the obtained ionic liquid is also included; Preferably, the obtained ionic liquid is repeatedly washed 3-7 times with deionized water; Preferably, the drying is vacuum drying, the drying temperature is 60-80° C., and the drying time is 10-14 h.

8. The method for preparing the underwater adhesive gel according to claim 1, Features: The molar ratio of lithium bis(trifluoromethanesulfonyl)imide to octyltrimethylammonium chloride is 1:0.8-1.2; Preferably, 0.5-1.5 mol of lithium bis(trifluoromethanesulfonyl)imide and 0.5-1.5 mol of octyltrimethylammonium chloride are added to each liter of water.

9. An underwater adhesive gel, Features: Prepared by the preparation method described in any one of claims 1 to 8.

10. Use of the underwater adhesive gel according to claim 9 in the preparation of underwater sensors, wherein the sensors include but are not limited to optical camouflage elements, motion detection elements, underwater communication elements, water temperature detection elements, water pressure detection elements or electrocardiogram detection elements.

Citation Information

Patent Citations

  • Anti-swelling adhesion ionic gel as well as preparation method and application thereof

    CN115894793A

  • In-situ phase separation ionic gel adhesive as well as preparation method and application thereof

    CN117447642A

  • Conductive ionic gel, preparation method and application of conductive ionic gel in aspects of amphibious sensing and drowning early warning

    CN118146458A

  • Photocuring 3D printing resin capable of self-healing ionic gel in water environment and preparation method and application of photocuring 3D printing resin

    CN118496430A

  • Gas separation ionic gel membrane as well as preparation method and application thereof

    CN118543256A